Toxicological aspects of wastewater - Ondrasik, Frantisek; Krocova, Sarka (European Journal of Chemistry, 2023)
‘Alea iacta est', the die is cast, said the Roman general Gaius Julius Caesar the moment he and his troops crossed the Rubicon River. This phrase refers to a state where everything has already been decided and this decision cannot be taken back. It is at this borderline that humanity now finds itself; its survival is at stake. The basic biogenic components of the environment, such as water, air, and soil, are coming under the pressure of the modern industrial revolution. The products of this anthropogenic activity significantly affect the environment. We live in a time of rapid climate change, melting of glaciers, devastation of nature, mass extermination, or loss of animal and plant species in order to increase human living standards. Man has caused all this in one stage of human life, a generation. Humanity mismanages natural resources and clings to a lifestyle that is vain. It destroys the natural environment on which it is dependent simultaneously. An environmental disaster is coming. Will our blue planet still be livable for future generations? The study deals with one of the components of the environmental environment, not an insignificant one, that is, water. For the moment, recycled water is a neglected and underappreciated resource from the point of view of the Czech Republic and its state authorities. The cleaning process may be inadequate or unreliable, and residual biological and chemical contaminants may pose a risk to human health. This work focuses on the use of purified wastewater mainly for firefighting unit activities in relation to a possible health risk. The result of the study is a clear possible recommendation for the use of recycled wastewater from a technical, technological, and logistical point of view, but taking into account the precautionary principle.